Governance and Tax Strategies: The Role of Firm Size in Affecting Tax Aggressiveness among Sharia-Listed Firms - Ratnawati, Juli; Hernawati, Retno Indah; Andika, Arditya Dian (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
This study investigates how corporate governance mechanisms influence tax aggressiveness in sharia-compliant firms listed on the Jakarta Islamic Index (JII), while examining the moderating role of firm size. Using a census sampling approach covering all JII-listed companies from 2022 to 2024, the research analyzes 90 firm-year observations. Multiple regression and moderated regression analyses test the direct and interaction effects of institutional ownership, independent commissioners, and audit committees on tax aggressiveness. The findings reveal that while institutional ownership does not significantly affect tax aggressiveness, the presence of independent commissioners and effective audit committees significantly reduces it. Firm size does not moderate these relationships, indicating that robust governance practices remain essential regardless of organizational scale. Importantly, this study integrates Islamic ethical principles such as justice (ʿadl), trustworthiness (amanah), accountability (hisbah), and the pursuit of public welfare (maslahah) to highlight the ethical dimensions of tax compliance in sharia-compliant firms. The results underscore the need for governance frameworks that not only meet regulatory requirements but also align with Islamic moral obligations, promoting transparency, fairness, and responsible corporate behavior.